Expression of nitric oxide synthase in kidney macula densa cells - Mundel, Peter; Bachmann, Sebastian; Bader, Michael; Fischer, Axel; Kummer, Wolfgang; Mayer, Bernd; Kriz, Wilhelm (Kidney international, 1992)
Expression of nitric oxide synthase in kidney macula densa cells. The distribution of nitric oxide synthase (NOS), the enzyme by which NO is generated from L-arginine, was investigated in rat kidney. The indirect immunofluorescence technique using a polyclonal antibody against type I NOS was applied, followed by the histochemical NADPH diaphorase staining technique on the same sections in order to demonstrate the enzymatic activity of NOS. Macula densa cells were strongly stained by both techniques, demonstrating abundant NOS in the cytoplasm of these cells. In addition, these findings were confirmed by nonradioactive in situ hybridization, thus demonstrating the corresponding messenger RNA in macula densa cells as well. Our findings provide the morphological basis for a possible role of NO as a mediator substance in signal transfer from distal tubular fluid to glomerular arterioles.
Artikelversion 18. Dezember 2015
Gesehen am 05.12.2023